Impact of a magnetic field on the thermodynamics of magnetized quark matter - Farias, R. L. S.; Timoteo, V. S.; Avancini, S.; Pinto, M. B.; Krein, G. [UNESP]; IOP (Iop Publishing Ltd, 2016)
We investigate the effect of a magnetic field on the thermodynamics of magnetized quark matter at finite temperature. By using the Nambu Jona-Lasino (NJL) model, we show that the lattice results for the quark consensate can be reproduced when the coupling constant G of the model decreases with the magnetic field and the temperature. Our results show that thermodynamic quantities and quark condensates are very sensitive to the dependence of G with the temperature, even in the absence of a magnetic field.